A Basic Two-Sector New Keynesian DSGE Model of the Indian Economy - KUMAR, Anshul (Theoretical and Practical Research in Economic Fields, 2023)
Indian economy is going through underlying changes in the post-pandemic recovery process. Effects of policies, monetary or fiscal, on macroeconomy need a thorough analysis in these recessionary times. In this context, this study develops a closed-economy DSGE model to see the impact of monetary policy on the Indian economy. The model includes price rigidities, and parameters are calibrated using the data on Indian economy. The model includes two sectors – intermediate goods and final goods producers, an inflation-targeting regime following the Taylor rule. Model is simulated for a positive productivity shock and an expansionary monetary policy shock. Results show that a positive productivity shock improves overall economic activity, and an expansionary monetary policy shock increases output for the short term only.